Nanostructural Evolution during Catalyst Layer Formation Studied via Cryo-Electron Microscopy. (24th August 2017) - Sugimori, Hidekazu; Terao, Takeshi; Nishino, Yuri; Ito, Yoshiko; Miyazawa, Atsuo; Konosu, Yuichi; Koga, Maito; Matsumoto, Hidetoshi; Uemura, Suguru; Kameya, Yuki; Sasabe, Takashi; Yoshida, Toshihiko; et al.
Abstract : The formation of a catalyst-layer structure induced by solvent evaporation of a catalyst ink was investigated by cryogenic scanning electron microscopy (cryo-SEM) and cryogenic transmission electron microscopy (cryo-TEM). Cryo-SEM and cryo-TEM reveal that the catalyst ink contains agglomerates of Pt/C catalyst particles that are several hundreds of nanometers to micrometers in size, and rod-like Nafion® particles that are around 3 nm in diameter. During the drying process, the Pt/C agglomerates are mutually connected in a network structure that resembles a spider web and that is induced by solvent evaporation, although this network structure is no longer observed after complete drying.